Occupational Hazards and the Practice of Prosthetic Dentistry - Ghani, Fazal; Weller, B. (Journal of Postgraduate Medical Institute, 2011)
The risks to the dental team from the increasingly hostile oral environment are now well recognized and publicized in the dental literature principally because of increased public and professional awareness of the potential dangers of cross infection involving HBV and HIV viruses.